Current Status of Alginate in Drug Delivery - Dewi Melani Hariyadi; Nazrul Islam (Hindawi Limited, 2020)
Alginate is one of the natural polymers that are often used in drug- and protein-delivery systems. The use of alginate can provide several advantages including ease of preparation, biocompatibility, biodegradability, and nontoxicity. It can be applied to various routes of drug administration including targeted or localized drug-delivery systems. The development of alginates as a selected polymer in various delivery systems can be adjusted depending on the challenges that must be overcome by drug or proteins or the system itself. The increased effectiveness and safety of sodium alginate in the drug- or protein-delivery system are evidenced by changing the physicochemical characteristics of the drug or proteins. In this review, various routes of alginate-based drug or protein delivery, the effectivity of alginate in the stem cells, and cell encapsulation have been discussed. The recent advances in the in vivo alginate-based drug-delivery systems as well as their toxicities have also been reviewed.